Prototype Social Distancing Reminder Using HC-SR04 Sensor At The Payment Counter Via A Smartphone - Ferry Wahyu Perdana; Shazana Dhiya Ayuni; Arief Wisaksono; Syamsudduha Syahrorini (Universitas Muhammadiyah Sidoarjo, 2021)
Starting from the beginning of March 2019 and even until the end of 2020, the Indonesian people are experienced prolonged suffering due to the emergence of a new type of infectious disease called Corona Virus 2019. Social Distancing is a program that aims to prevent the transmission of the COVID-19 disease as early as possible. In this research, the method used is the observation technique and literature study for the implementation of the HC-SR04 sensor as one of the distance sensors used for distance reminders implemented in public spaces using IoT as a monitoring system. The results obtained are the reading accuracy of the HC-SR04 sensor is quite accurate to 100% accuracy and when the HC-SR04 sensor detects less than 8cm (1meter real distance) then the DF Player will sound, the LCD will display a display “Jaga Jarak Anda!